"Choledochoscope" as an Important Addition in Difficult Airway Management: A Case Report. Issue 5 (1st March 2020) - Poudel, Anjali; Pokharel, Krishna; Jaisani, Mehul Rajesh
Abstract : The choledochoscope is an additional tool to manage a difficult airway. We successfully used it for the first time for awake nasal intubation in a patient with no mouth opening resulting from bilateral temporomandibular ankylosis. The visual appearance of the airway structures was not compromised. However, the shorter length and larger diameter of the choledochoscope in comparison with the fiberoptic bronchoscope are crucial limiting factors of this method. We, therefore, suggest considering a choledochoscope for intubation in patients with difficult airway as a second-line alternative when a fiberoptic bronchoscope is not available.